2022
DOI: 10.3389/fnint.2022.821850
|View full text |Cite
|
Sign up to set email alerts
|

Resting Rates of Blood Flow and Glucose Use per Neuron Are Proportional to Number of Endothelial Cells Available per Neuron Across Sites in the Rat Brain

Abstract: We report in a companion paper that in the mouse brain, in contrast to the 1,000-fold variation in local neuronal densities across sites, capillary density (measured both as capillary volume fraction and as density of endothelial cells) show very little variation, of the order of only fourfold. Here we confirm that finding in the rat brain and, using published rates of local blood flow and glucose use at rest, proceed to show that what small variation exists in capillary density across sites in the rat brain i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
3

Relationship

3
4

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 48 publications
1
8
0
Order By: Relevance
“…What makes it a good proxy is that local capillary density in fixed brain tissue correlates very well, and linearly, with resting blood flow and local rate of glucose use in both rat ( Klein et al, 1986 ; Borowsky and Collins, 1989 ) and macaque brains ( Noda et al, 2002 ). A direct validation of the correspondence between local capillary density and resting metabolic rate is reported in the accompanying study ( Ventura-Antunes et al, 2022 ), in which we find that the small variations in the local vascular fraction measured as in the present study across sites in the rat brain are a very good approximation of measurements of local energy cost at rest in each structure. We thus expect that systematic analyses of local capillary densities will provide a powerful tool to circumvent the limitations to studying energy use per neuron in living animals, and open the way to comparative studies of energy availability per neuron in brains of species that are unlikely ever to be brought alive to laboratory settings.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…What makes it a good proxy is that local capillary density in fixed brain tissue correlates very well, and linearly, with resting blood flow and local rate of glucose use in both rat ( Klein et al, 1986 ; Borowsky and Collins, 1989 ) and macaque brains ( Noda et al, 2002 ). A direct validation of the correspondence between local capillary density and resting metabolic rate is reported in the accompanying study ( Ventura-Antunes et al, 2022 ), in which we find that the small variations in the local vascular fraction measured as in the present study across sites in the rat brain are a very good approximation of measurements of local energy cost at rest in each structure. We thus expect that systematic analyses of local capillary densities will provide a powerful tool to circumvent the limitations to studying energy use per neuron in living animals, and open the way to comparative studies of energy availability per neuron in brains of species that are unlikely ever to be brought alive to laboratory settings.…”
Section: Discussionsupporting
confidence: 85%
“…The two capillary density-related variables are correlated within each structure individually ( Table 6 ), and there is good overlap in data points across structures and animals, especially in the larger 2D dataset ( Figure 4A , right), where the overlapping power relationships ( Table 6 ) indicate that the relationship between capillary fraction and cellular composition of capillaries is shared throughout the brain. This agreement suggests that endothelial cell density is a good proxy for the resting rates of blood flow and glucose use ( Klein et al, 1986 ; Noda et al, 2002 ; Ventura-Antunes et al, 2022 ).…”
Section: Resultsmentioning
confidence: 63%
“…Consistent with our proposition that rCBF o is determined by the physical properties of the local capillary bed are the results of empirical studies that measured capillary density and rCBF o and observed, as predicted, that rCBF o (and also rCMR glu ) in the undisturbed awake state is strongly linearly correlated with local capillary density (Klein et al, 1986;Borowsky and Collins, 1989). Figure 4 shows experimental results of a linear relationship between regional cerebral metabolic rate of glucose consumption (rCMR glc ) or blood flow and local capillary density (see also Ventura-Antunes et al, 2022), as predicted from the metaanalysis in Figure 2 and Eq. [4].…”
Section: Anatomical Evidence For the Relationship Between Do' And Cap...mentioning
confidence: 67%
“…Only further studies will establish whether the difference applies to astrocytes, oligodendrocytes, microglial cells, or vasculature, but any clade-specific increases in capillary densities in the brain, if they happened, would have important consequences for the range of possibilities of brain cellular composition. We recently found that relatively uniform capillary densities in the rat brain make it so that in sites with larger densities of neurons, there is less energy available per individual neuron (Ventura-Antunes et al, 2022). In mammals, the sharply decreased densities of neurons in brain structures that gained more neurons (and thus became larger) offers the advantage, from the viewpoint of single neuron physiology, of increased energy availability per neuron (which may still not be sufficient to compensate for the increased cost of larger neuronal cell size; Ventura-Antunes et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…We recently found that relatively uniform capillary densities in the rat brain make it so that in sites with larger densities of neurons, there is less energy available per individual neuron (Ventura-Antunes et al, 2022). In mammals, the sharply decreased densities of neurons in brain structures that gained more neurons (and thus became larger) offers the advantage, from the viewpoint of single neuron physiology, of increased energy availability per neuron (which may still not be sufficient to compensate for the increased cost of larger neuronal cell size; Ventura-Antunes et al, 2022). With mammal-like capillary densities in the brain, the higher neuronal densities characteristic of bird brains might impose extreme restrictions on neuronal activity and not be viable.…”
Section: Discussionmentioning
confidence: 99%